Fabrication of composite block from beta-tricalcium phosphate and polyacrylic acid via freeze-drying method - Rosalina Tjandrawinata; Eddy; Rafhaela Johanna Halim; Thet Thet Swe; Tansza Setiana Putri (Dental Journal (Majalah Kedokteran Gigi), 2026)
Background: Beta-tricalcium phosphate (β-TCP) is widely used in bone grafting due to its biocompatibility and bioresorbability. Recently, there has been growing interest in using sustainable materials, such as green mussel shells, as an alternative source for β-TCP. These shells, rich in calcium carbonate, provide a cost-effective and environmentally friendly alternative for β-TCP synthesis. Purpose: To fabricate composite blocks from β-TCP derived from green mussel shells, mixed with polyacrylic acid (PAA), using a setting reaction and freeze-drying method. Methods: Beta-tricalcium phosphate powder was obtained via wet precipitation, starting with calcium carbonate from green mussel shells, converting it to calcium oxide, and then to β-TCP. The resulting powder was mixed with PAA, set, and freeze-dried to form composite blocks. Results: Characterization of the composite blocks for porosity and diametral tensile strength (DTS) showed that blocks made with green mussel shell-derived β-TCP had rougher surfaces due to larger particles than control blocks made with commercial β-TCP. Composite blocks with 70% green mussel shell-derived β-TCP and 30% PAA exhibited significantly higher porosity (26.97% ± 2.64%) and DTS (11.76 ± 1.59 MPa) than those made with commercial β-TCP (porosity: 13.40% ± 1.56%; DTS: 7.79 ± 1.29 MPa). Reducing β-TCP content to 60% resulted in increased porosity (34.22% ± 1.84%) and lower DTS (6.41 ± 0.78 MPa). Conclusion: Composite blocks made from green mussel shell-derived β-TCP and PAA showed higher porosity and significantly higher DTS than blocks made from commercial β-TCP. Decreasing β-TCP content increased porosity but decreased DTS.